2005
DOI: 10.2166/wst.2005.0120
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of different measures for improving removal in a stormwater pond

Abstract: The effect of retrofitting an existing pond on removal efficiency and hydraulic performance was modelled using the commercial software Mike21 and compartmental modelling. The Mike21 model had previously been calibrated on the studied pond. Installation of baffles, the addition of culverts under a causeway and removal of an existing island were all studied as possible improvement measures in the pond. The subsequent effect on hydraulic performance and removal of suspended solids was then evaluated. Copper, cadm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…These observations are consistent with several previous studies (e.g. German et al, 2005;Khan et al, 2013). However, while previous researchers did not attempt to model stem-scale mixing processes occurring within the vegetation, these effects were represented in the current work.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These observations are consistent with several previous studies (e.g. German et al, 2005;Khan et al, 2013). However, while previous researchers did not attempt to model stem-scale mixing processes occurring within the vegetation, these effects were represented in the current work.…”
Section: Discussionsupporting
confidence: 93%
“…Tsavdaris et al (2014) showed similar recirculation zones in non-vegetated ponds. German et al (2005) modelled a nonvegetated stormwater pond with an island and showed a recirculation zone similar to the one visible in Figure 4(c) formed around their island. Interestingly, removing their island did not alter the RTD.…”
Section: Discussionmentioning
confidence: 85%
“…The hydraulic efficiency, λ, lies within the wider context of hydraulic performance, and is a measure expressing the combined effects of the distribution of incoming water in the system and of the amount of mixing in the system (Persson et al, 1999). Several studies have investigated factors that influence hydraulic performance of CWs and ponds, and have tried to optimise the systems and to provide general design guidelines (Aguwamba, 2006;Bodin et al, 2012;Diaz et al, 2012;German et al, 2005;Holland et al, 2004;Jadhav & Buchberger 1995;Koskiaho, 2003;Persson et al, 1999;Persson, 2000;Somes et al, 1999;Su et al, 2009;Wörman & Kronnäs, 2005). Nevertheless, the majority of those studies was either conducted via simulations (which overlooks the field effects), or has neglected vegetation (which affects the hydrodynamics).…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing of pond geometry for higher removal rates has been investigated in various studies e.g. [18], [12], [20], [7] and [8]. It is generally agreed that the removal efficiency varies from one facility to another [18] and from one event to another, even including negative efficiencies due to short circuiting flow, resuspension, release of pollutants due to changes e.g.…”
Section: Introductionmentioning
confidence: 99%